Multicultural pedagogy: contextualized classes mark a new time in the amazon (Research, Society and Development, 2022)
This article describes activities developed in the classroom in the Brazilian Amazon that consider the context and everyday life. It is part of the project Multiculturalism and mathematical ideas in sociocultural practices: possibilities for the process of teaching mathematics in the state of Amazonas, in progress in the Programa de Pós-graduação da Faculdade de Educação da Universidade Federal do Amazonas – PPGE/UFAM. Its main objective is to understand how the mathematical ideas involved in the activities of different and differentiated communities interfere in the teaching and learning process. The research is of the exploratory type, with a quali/quanti approach, since it uses both statistical methods to substantiate the argumentation, and goes through phenomenological processes, characteristic of qualitative research. Among the results, we highlight the group of teachers in schools and training centers working on multicultural pedagogy, teaching Mathematics that involves regional elements, daily activities that emphasize Ethnomathematics, understood here as the teaching of Mathematics through a cultural bias. New groups that practice meaningful and contextualized teaching based on the ideas of multiculturalism are expected to be encouraged, which can contribute to school performance, appreciation of diversity, Amazonian culture and, discussion of the search for the forgotten, emptied, silenced secular culture.